Management of Prehypertension: Current Status and Future Strategies - Sasamura, Hiroyuki; Itoh, Hiroshi; Julius, Stevo (Current Hypertension Reviews, 2011)
Prehypertension is known to be a risk factor for hypertension and cardiovascular disease. If prehypertension is left untreated, the blood pressure continues to increase due to multiple accelerators which facilitate the development of hypertension. Studies using animal models of hypertension suggested that interruption of these mechanisms by transient inhibition of the renin-angiotensin system (RAS) attenuates the development of hypertension. The TROPHY study provided clinical evidence that pharmacological intervention in the prehypertensive stage may suppress subsequent development of hypertension. Recently, we reported that high dose angiotensin inhibition in spontaneously hypertensive rats (SHR) with established hypertension caused a significant regression of hypertension, and we have started a prospective, multi-center clinical study (STAR CAST study) to examine if regression from hypertension back to prehypertension may also be feasible in humans. Since prehypertension is increasingly recognized as an important public health issue, further studies to assess strategies for attenuating the progression from prehypertension to hypertension are required.
Keywords: hypertrophy